Psychotropic medication prescribing in people with autism spectrum disorders with and without psychiatric comorbidity. (March 2023) - Carthy, Elliott; Ross, Callum; Murphy, David
SUMMARY: Autism spectrum disorders (ASDs) are a group of lifelong neurodevelopmental disorders characterised by difficulties in social interactions and social communication, and restricted and repetitive behaviours. Relative to the general population, individuals with ASDs are likely to be overrepresented in secure psychiatric care and custodial settings. Outcomes vary and can be problematic in the context of co-occurring intellectual disability, psychiatric disorder and challenging behaviours. To date, there is little in the way of specialised clinical guidance on the prescription of psychotropic medicines for individuals with ASDs, particularly information on any differences in efficacy and/or tolerability of specific medications. This review summarises the key research to date on the prescription of psychotropic medication in ASD with and without comorbid psychiatric or neurodevelopmental disorders, within the context of the existing clinical guidance. Some critical analysis is provided to aid clinicians in following a safe, effective and individualised approach to prescribing for people with ASDs.